2022
DOI: 10.1159/000527775
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Dentin Pellicle and the Impact of Erosion

Abstract: While the ultrastructure of the enamel pellicle and its erosion protective properties are well studied, the dentin pellicle is still neglected in dental research. Therefore, the ultrastructure and erosion protective properties of a pellicle formed on bovine dentin specimens was investigated in the present study. The dentin pellicle was formed in-situ for 3, 30, 120, and 360 min at buccal or palatal oral sites of 3 subjects and analyzed by transmission electron microscopy. In order to clarify the impact of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The pellicle and in particular the basal layer acts as a diffusion barrier, thereby protecting enamel against dental erosion [11]. In contrast, the protective properties of the dentin pellicle are controversially discussed [12], which could be related to the missing basal layer [13]. A promising approach to enhance the protective properties of the pellicle is the modification of its ultrastructure by polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…The pellicle and in particular the basal layer acts as a diffusion barrier, thereby protecting enamel against dental erosion [11]. In contrast, the protective properties of the dentin pellicle are controversially discussed [12], which could be related to the missing basal layer [13]. A promising approach to enhance the protective properties of the pellicle is the modification of its ultrastructure by polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…This might influence the mechanical properties of the teeth ( 24 ). However, full protection of the teeth by the pellicle is not possible ( 25 ). Hara et al showed that the dental pellicle formed after 2 h can protect teeth from demineralization due to erosive challenge for 10 min, but not a longer period.…”
Section: Introductionmentioning
confidence: 99%